2003
DOI: 10.1016/s0009-2614(02)01858-4
|View full text |Cite
|
Sign up to set email alerts
|

Comment on ‘Rate coefficients for photoinitiated NO2 unimolecular decomposition: energy dependence in the threshold regime’ [Chem. Phys. Lett. 358 (2002) 71]

Abstract: Recently, Wittig and co-workers have published rate coefficients kðEÞ for the unimolecular decomposition of photoinitiated NO 2 close to the dissociation threshold [Chem. Phys. Lett. 358 (2002) 71]. They found out that kðEÞ for low angular momentum J exhibits a strong increase within 25 cm À1 of the reaction threshold. The authors emphasize that their experimental results are surprising and cannot be understood quantitatively on the basis of current theory on NO 2 . In this Comment we demonstrate that recent q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…However, the disparate spectral resolution associated with each experimental setup has to be considered. Resonance width fluctuations, over an energy range of ∼20 cm −1 , are in agreement with the quantum mechanical calculations based on a 3D-PES of Schinke's group 44,48,59 and with PST. Despite these quantum fluctuations, we report on the unimolecular dissociation coefficients relatively to the opening of the two first dissociation channels NO 2 …”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…However, the disparate spectral resolution associated with each experimental setup has to be considered. Resonance width fluctuations, over an energy range of ∼20 cm −1 , are in agreement with the quantum mechanical calculations based on a 3D-PES of Schinke's group 44,48,59 and with PST. Despite these quantum fluctuations, we report on the unimolecular dissociation coefficients relatively to the opening of the two first dissociation channels NO 2 …”
Section: Introductionsupporting
confidence: 85%
“…We concluded that our data agree with those of Tsuchiya's group 38 and we mainly valid the PST approach, 40,104 and the hypothesis of loosely bound transition states in the probed excess energy range despite the fact that we did not study the photofragments. This conclusion may disagree with time-resolved measurements, 44,47,59 while the move of the transition states from loosely to tightly bounding has been suggested as a plausible way to reconcile the different experimental observations. However, the disparate spectral resolution associated with each experimental setup has to be considered.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In the picosecond time range, the dynamics are known to be complex. Individual resonances show strongly varying dissociation constants close to the dissociation threshold, leading to excitation-energy-dependent dissociation times 62,63 . In picosecond and femtosecond time-resolved experiments, due to the bandwidth of the excitation pulse and the associated spectral averaging, a monotonic increase of the dissociation rates with increasing excitation energies 64,65 has been reported (see crosses in fig.…”
Section: B Vibronic Wave Packetsmentioning
confidence: 99%